2010
DOI: 10.1007/s10815-010-9470-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of early pregnancy and neonatal outcomes after frozen and fresh embryo transfer in ART cycles

Abstract: Purpose Frozen embryo transfer (FET) has no clear negative impact on neonatal outcome compared with fresh embryo transfer (ET) and appears to result in similar or even better neonatal outcome. The objective of this study was to compare early pregnancy outcome and neonatal health of children born after FET and fresh ET. Methods In this study early pregnancy and neonatal outcomes after FET (n=200) and fresh ET (n=500) were compared. Results For early pregnancy, biochemical pregnancy was comparable between FET an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
4
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 28 publications
5
47
4
2
Order By: Relevance
“…On the contrary to our results, Aflatoonian et al (3) found that spontaneous abortion rate in FET group was significantly higher than in fresh ET group .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…On the contrary to our results, Aflatoonian et al (3) found that spontaneous abortion rate in FET group was significantly higher than in fresh ET group .…”
Section: Discussioncontrasting
confidence: 99%
“…Basirat et al, 2016 (1) documented non-significant difference of the biochemical pregnancy rate (23% in FET versus 18.8% in fresh embryo transfer). Alike, Aflatoonian et al, (3) reported that biochemical pregnancy rate was 27% (54200/) in the FET group versus 22.1% (122500/) in the fresh embryo transfer group.Also, Check et al 16 obtained a significantly higher pregnancy rate in frozen-thawed embryo than fresh embryo transfer in recipients patients (63.4 versus 43.6 %) attributed to the absence of high serum Estradiol in the recipients patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been concerns about the impact of cryopreservation on the health of children born, outcome data after frozen ET have been generally reassuring (3). Results of a number of observational studies (4)(5)(6) indicate that obstetric and perinatal outcomes in pregnancies resulting from cryopreserved embryos are similar to those in fresh IVF/ intracytoplasmic sperm injection (ICSI) cycles, whereas other investigators suggest that they are superior (7,8). Currently, there are no randomized controlled trials that have compared obstetric and perinatal outcomes after elective cryopreservation of all embryos followed by delayed transfer versus fresh ET in an IVF/ICSI cycle, which is the current practice in almost all IVF units.…”
mentioning
confidence: 99%
“…17 However, there were some studies reporting no difference of live birth weight between fetuses after FTET and FET. 18,19 Some results of studies related to the perinatal/obstetric outcome may be inconsistent, and they are mainly observational studies, thus it is considered that more randomized controlled studies are needed in the future. According to the 2017 Cochrane systemic review, FTET was associated with fewer miscarriages, a higher birth weight of singleton babies, and an increased rate of pregnancy complications.…”
Section: 5mentioning
confidence: 99%